Electrospinning of uniform nanofibers of Polymers of Intrinsic Microporosity (PIM-1): The influence of solution conductivity and relative humidity. (12th September 2019) - Topuz, Fuat; Satilmis, Bekir; Uyar, Tamer
Abstract: Polymers of Intrinsic Microporosity (PIMs) are ultra-permeable macromolecules, which can be cast as a dense membrane and exploited in a wide spectrum of applications, particularly for gas separation owing to their extremely large inner surface area, free volume and high gas permeability. While they are mostly intended to serve as membranes for gas separation, in recent years, they have been also employed in water treatment applications owing to their solution processability, which enables the production of fibrous membranes by electrospinning. The fibrous form provides an increase in sorption performance, water permeability and flux for their application in water treatment. However, owing to the low conductivity of PIM-1 solutions in 1, 1, 2, 2-tetrachloroethane (TeCA) that is the ideal solvent for the electrospinning of PIM-1 solutions, a higher polymer concentration is required to produce bead-free fibers. Furthermore, the electrospinning of highly concentrated PIM-1 solutions leads to the formation of microfibers. To tackle these problems, we herein incorporated an ammonium salt (i.e., tetraethylammonium bromide, TEAB) to increase the conductivity of PIM-1 solutions and study the impact of solution conductivity on the electrospinning of PIM-1 solutions. In parallel to the conductivity study, the influence of relative humidity on the electrospinning and morphology of PIM-1 fibers was explored. The addition of TEAB significantly increased the solution conductivity and drastically enhanced the electrospinnability of PIM-1. The electrospinning of PIM-1 solutions (10% (w/v)) in the presence 7.5 wt% TEAB (with respect to PIM-1) led to bead-free fibers, while at the same concentration, electrosprayed beads and droplet splashing were observed in the absence of TEAB. On the other hand, increasing humidity did not influence the electrospinnability of PIM-1 and the fiber texture, however, less fibers were formed in a given time at very high humidity conditions (~80%). Overall, the experimental findings revealed that the addition of the salt drastically enhanced the electrospinnability of PIM-1 solutions owing to the enhanced conductivity and could lead to the formation of very thin PIM-1 fibers with 160 nm in diameter while no significant effect of relative humidity on the electrospinnability of PIM-1 solutions was observed. Graphical abstract: The influence of solution conductivity and relative humidity on the electrospinning of PIM-1 was studied, and the experimental findings revealed that higher solution conductivity significantly improved the electrospinnability of PIM-1 solutions, while relative humidity had no drastic influence on the electrospinnability of PIM-1.Image 1 Highlights: The conductivity of PIM-1 solutions was significantly increased by salt addition. Higher salt content drastically improved the electrospinnability of PIM-1 solutions. Very thin PIM-1 fibers with 160 nm in diameter could be produced by salt addition. Increasing relative humidity did not influence the electrospinnability of PIM-1. Less fibers were formed at very high humidity conditions (~80%) in a given time.